Why Don't We Play Pandemic? Analog Gaming Communities in Lockdown. (3rd March 2021) - Coward-Gibbs, Matt
Abstract: This short response demonstrates the way in which COVID-19 has impacted analog gamers and their leisure practices. Analog gameplay, often referred to by its moniker – tabletop gaming – is jokingly referred to by many of its players as the perfect activity for self-isolation. As such, throughout this response, I consider the resilience of analog play in the wake of a global crisis, considering the way in which digital technologies, gaming lifestyles and humour provide comfort, social interaction and a level of normalcy to their players in the wake of global uncertainty.